Broad phylogenetic analysis of cation/proton antiporters reveals transport determinants - Gal Masrati (Nature Portfolio, 2018)
Cation/proton antiporters (CPAs) play a major role in maintaining living cells’ homeostasis and are divided in two main groups: CPA1 and CPA2. Here authors use a comprehensive evolutionary analysis of 6537 representative CPAs and reveal a sequence motif that determines central phenotypic characteristics.